With a hammer [compact disc] - Yaeji, 1993- (XL Recordings, 2023)
Yaeji is a NYC-via-Seoul producer, DJ, and vocalist, whose introspective, dancefloor-ready tracks have made her a global icon occupying a space all her own. After breaking out with her 2017 debut EPs that featured singles "Raingurl" and "Drink I'm Sippin On," the multifaceted artist featured on Charli XCX's 2019 album Charli, has gone onto produce remixes for Dua Lipa, and Robyn, collaborate with the beloved Seoul-based polymath OHHYUK, sell out two headlining worldwide tours, and launch her bespoke lifestyle webstore JI-MART. Her highly anticipated debut album sees Yaeji excavating her inner world with full force, resulting in her most thrilling and personal work yet.